Tonight we die as men : the untold story of Third Battalion 506 Parachute Infantry Regiment from Toccoa to D-Day /: the untold story of Third Battalion 506 Parachute Infantry Regiment from Toccoa to D-Day. (2009) - Unknown
No abstract available